Comparison between incorporation and conventional fabrication techniques of diopside-based glass-ceramics - Wipada Senanon (2019)
© 2019 Elsevier B.V. Crystallization kinetics was widely used for studying nucleation and crystallization mechanism in the materials. In this study, the crystallization kinetics via non-isothermal method of diopside glass-ceramics prepared by incorporation and conventional techniques, have been investigated. The difference between incorporation and conventional method is the use of a simple mixed-oxide technique for producing diopside powder and the powder is then mixed with a glass batch while that of conventional one uses only simple oxides as starting precursors. Therefore, in this work, the diopside powder was calcined at 1200 °C for 4 h and subsequently mixed with SiO2, Al2O3 and ZnO in the 30CaMgSi2O6:40SiO2 + 20Al2O3 + 10ZnO (mol%). For, the conventional method, the simple oxide powders of CaMgSi2O6 (stoichiometric composition) were used instead of the calcined CaMgSi2O6 powders, in similar glass formula. From the heating rate dependence on crystallization temperature, the activation energy (Ea) of crystallization and Avrami parameter (n) were calculated by Kissinger and Ozawa equation, respectively. It was found that these two methods show similar crystallization mechanism but the incorporation method tends to crystallize easier than that of conventional one.